Sistem Reservasi on Line dan Penerapan Metode Servqual pada Hotel TriJaya Cirebon - Julianti Kasih; Gabriela Stefiyani Suprato (Jurnal Teknik Informatika dan Sistem Informasi, 2017)
Abstract — Information and technology are growing rapidly and are being used in numerous fields. Hotel industry is one of the many fields that utilize information and technology. Hotel is an industry that provides lodging services, food, and also some other services. TriJaya is a hotel that's located in Cirebon. This hotel does not a website yet, so customers need to come to the hotel and manually process their reservation. These reservation processes will be a lot more difficult if there are a lot of customers at the same time, which will increase the probability of human error and make the customers less satisfied. With the establishment of reservation, online services, and customer satisfaction measurement website, the hotel reservation services will be easier; food services will be easier, and will also help maintain the hotel quality. Servqual is a method to measure quality and customer satisfaction from a number of viewpoints. The measurement result will be used to make the hotel aware of their average customer satisfaction and also to identify which part of the services needs to be improved. This website is expected to support the business process and solve the problems that this hotel currently has. Keywords— hotel, services, reservation, servqual, survey.